TOURISM SECTOR ANALYSIS OF ORIGINAL INCOME OF THE GRESIK DISTRICT - Sri Setiawati, Ririt Iriani; Tri Pamudya, Mochammad Akbar; Vizandra, Ellyzabeth Putri; Habibie, Samas Adimisa Mishbah; Islamudin, Ardhi (JEA17: Jurnal Ekonomi Akuntansi, 2024)
In realizing national development, the central government and local governments also have an important role in the success of national development, so the central government imposes decentralization which aims to provide full discretion to the regions in realizing responsible autonomous regions, to regulate and manage the interests of the community in accordance with the conditions and potential possessed by the region. One of the decentralization can be seen from the number of visits, the number of tourist attractions and the number of hotels in the Gresik Regency area. The research was conducted on the number of visits, the number of tourist attractions and the number of hotels in Gresik Regency. This study uses primary data with secondary data collection techniques. The analysis test was carried out with classical assumptions, hypothesis testing and data processing using SPSS version 25. The results of the data analysis test indicate that simultaneously the number of visits, the number of tourist attractions and the number of hotels have an effect on local revenue. And partially the number of visits, the number of tourist attractions and the number of hotels together have an effect on local revenue. The conclusion of this study is that the independent variables, namely the number of visits, the number of tourist objects, and the number of hotels, simultaneously and partially affect the dependent variable, namely local revenue in Gresik Regency.